PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA LPD DESA ADAT ABIANSEMAL - I Gede Yudha Ari Pradana; Pande Ketut Ribek; Tiksnayana Vipraprastha (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
The success of a company can be seen from the performance of employees. Employee performance is the employee's ability to do something with certain skills. There are several factors that influence employee performance, namely organizational commitment, organizational culture and job satisfaction. This study aims to determine the effect of organizational commitment, organizational culture and job satisfaction on the performance of LPD Abiansemal Traditional Village employees. The population in this study were all employees of the Abiansemal Traditional Village LPD. Determination of the sample with saturated sampling technique with a total sample of 35 employees. Methods of data collection by observation, interviews, documentation, and questionnaires. The data analysis technique used is multiple linear regression analysis. The test results show that organizational commitment has a positive and significant effect on the performance of LPD Abiansemal Traditional Village employees, this means that an increase in organizational commitment will be followed by an increase in employee performance. Organizational culture has a positive and significant effect on the performance of LPD Desa Adat Abiansemal employees, this means that the better the organizational culture, the better the employee performance. Job satisfaction has a positive and significant effect on the performance of the Abiansemal Traditional Village LPD employees, this means that the higher the employee job satisfaction, the higher the performance of the Abiansemal Traditional Village LPD employees.